Prognostic value of neutrophil‐to‐lymphocyte ratio in patients with metastatic castration‐resistant prostate cancer receiving prostate‐specific membrane antigen targeted radionuclide therapy - Stangl‐Kremser, Judith; Sun, Michael; Ho, Benedict; Thomas, Joseph; Nauseef, Jones T.; Osborne, Joseph R.; Molina, Ana; Sternberg, Cora N.; Nanus, David M.; Bander, Neil H.; Tagawa, Scott (The Prostate, 2023)
Background Neutrophil count:lymphocyte count ratio (NLR) may be a prognostic factor for men with advanced prostate cancer. We hypothesized that it is associated with prostate‐specific antigen (PSA) response and survival in men treated with prostate‐specific membrane antigen (PSMA)‐targeted radionuclide therapy (TRT). Methods Data of 180 men with metastatic castration‐resistant prostate cancer (mCRPC) who were treated in sequential prospective radionuclide clinical trials from 2002 to 2021 (utilizing 177Lu‐J591, 90Y‐J591, 177Lu‐PSMA‐617, or 225Ac‐J591) were retrospectively analyzed. We used a logistic regression to determine the association between NLR and ≥50% PSA decline (PSA50) and a Cox proportional hazards model to investigate the association between NLR and overall survival (OS). Results A total of 94 subjects (52.2%) received 177Lu‐J591, 51 (28.3%) 177Lu‐PSMA‐617, 28 (15.6%) 225Ac‐J591, and 7 (3.9%) 90Y‐J591. The median NLR of 3.75 was used as cut‐off (low vs. high NLR; n = 90, respectively). On univariate analysis, NLR was not associated with PSA50 (HR 1.08; 95% confidence interval [CI] 0.99–1.17, p = 0.067). However, it was associated with worse OS (hazard ratio [HR] 1.06, 95% CI 1.02–1.09, p = 0.002), also after controlling for circulating tumor cell count and cancer and leukemia group B risk group (HR 1.05; 95% CI 1.003–1.11, p = 0.036). Men with high NLR were at a higher hazard of death from all causes (HR 1.43, 95% CI 1.05–1.94, p = 0.024). Conclusions NLR provides prognostic information in the setting of patients with mCRPC receiving treatment with PSMA‐TRT.